HIV Dynamics: Virology, Host Response, and Evolving Treatment Paradigms - Mr. Bobade Sanket S.; Ms. Deshmukh Shraddha N.; Ms. Chandel Pratiksha B.; Dr. Gunjegaonkar Shivshankar M.; Dr. Joshi Amol A. (Research Retrieval and Academic Letters, 2025)
Human Immunodeficiency Virus (HIV), a retrovirus from the Lentivirus genus, targets CD4+ T cells, leading to immune system deterioration and potentially Acquired Immunodeficiency Syndrome (AIDS). HIV-1, more virulent than HIV-2, drives most global infections. The virus enters host cells via CD4 and co-receptors (CCR5/CXCR4), undergoes reverse transcription, and integrates into the host genome, enabling latency or replication. Chronic immune activation and CD4+ depletion characterize pathogenesis, progressing to AIDS without treatment. Transmission occurs through bodily fluids, with high-risk groups including men who have sex with men and injecting drug users. Antiretroviral therapy (ART), notably regimens like Tenofovir, Lamivudine, and Dolutegravir, suppresses viral load, enhancing immune function. Non-pharmacological interventions, including cognitive therapy and lifestyle modifications, complement ART. In India, the National AIDS Control Organisation’s “Test and Treat” policy ensures universal ART access, significantly reducing HIV transmission and improving outcomes.